Evaluasi Penerapan Marketing Mix 7P pada Layanan Rawat Jalan Eksekutif : Studi Kasus Rumah Sakit Nirmala Suri Sukoharjo - Lestari, Tri; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the implementation of the marketing mix strategy (7P) in the Executive Outpatient Services at Nirmala Suri Hospital, Sukoharjo. The background of this research is based on the significant decline in patient visits over three consecutive years, from 5,493 visits in 2022 to 5,048 in 2023, and only reaching 5,436 in 2024, well below the target of 10,000 visits per year. This study uses a descriptive qualitative approach with in-depth interviews, observations, and documentation with 111 informants. The results indicate that the aspects of process (28%), physical evidence (22%), and human resources (19%) are the most appreciated marketing mix elements by patients. Weaknesses were found in the promotional strategy, which has not been optimal, the inaccuracy of doctors' schedules, and the lack of supporting facilities such as lactation rooms and children's play areas. Strategic recommendations include enhancing digital promotion, improving the registration and queuing system, strengthening human resources training, and adding physical facilities to reinforce the premium service image. These findings are expected to serve as a foundation for managerial decision-making in improving competitiveness and patient loyalty.